2010
DOI: 10.1167/iovs.09-5032
|View full text |Cite
|
Sign up to set email alerts
|

An Agonistic TrkB mAb Causes Sustained TrkB Activation, Delays RGC Death, and Protects the Retinal Structure in Optic Nerve Axotomy and in Glaucoma

Abstract: In animal models of acute and chronic neurodegeneration, a TrkB agonist affords long-lasting neuroprotection by causing sustained TrkB activation. The use of structural end points could have prognostic value to evaluate neuroprotection. This work contributes to the understanding of neurotrophic mechanisms underlying RGC death in glaucoma and optic nerve axotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 47 publications
0
80
0
Order By: Relevance
“…Fluorogold Retrograde Labeling-RGCs were retrogradely labeled with a 4% Fluorogold solution (Fluorochrome, Englewood, CO) applied bilaterally to the superior culliculous (4,11), with minor modifications as described (5). In ON, axotomy retrograde labeling was performed 7 days before surgical transection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorogold Retrograde Labeling-RGCs were retrogradely labeled with a 4% Fluorogold solution (Fluorochrome, Englewood, CO) applied bilaterally to the superior culliculous (4,11), with minor modifications as described (5). In ON, axotomy retrograde labeling was performed 7 days before surgical transection.…”
Section: Methodsmentioning
confidence: 99%
“…OCT is a non-invasive method that allows time kinetic studies in the same animal, acquisition of retinal images with axial tissue resolution nominally better than 4 m, and repeatability of the measurements from B-scans better than 1 m. Details of the method have been published (5). During retinal scanning, 3 volumes were acquired in different sectors of the retina containing the ON head and retinal blood vessels as landmarks.…”
Section: Quantification Of Retinal Structures Using Fourier Domain Opmentioning
confidence: 99%
“…Another approach consists on the selective stimulation of trophic factor receptors using specific agonists. Thus, it has been shown that a selective agonist of TrkB (BDNF receptor) causes a long term TrKB activation and significantly delays RGC degeneration after IOP increase and after optic nerve transection (Bai et al, 2010). Brimonidine, an α-2 adrenergic agonist, has been shown to neuroprotect RGCs after retinal ischemia (Lafuente et al, 2001Lafuente Lopez-Herrera et al, 2002;Vidal-Sanz et al, 2001a,b, 2007Aviles-Trigueros et al, 2003;Mayor-Torroglosa et al, 2005;Lonngren et al, 2006), after optic nerve crush (Wheeler et al, 1999) and after laser-induced ocular hypertension Lambert et al, 2011).…”
Section: Therapies To Increase the Resistance Of The Injured Neuronsmentioning
confidence: 99%
“…This ob ser va tion was reproduced by other groups [42,55,56], but results also trig gered scepticism regarding the magnitude and duration of exogenously ad ministered BDNF [57][58][59]; these latter workers also attempted co-ad mi ni stration with radical scavengers, gene therapy and more long-lasting synthetic TrkB agonists, and despite positive data in these animal models, no clinical studies with topical instillation of BDNF have been carried out. Domenici et al [60] investigated the utility of exogenous BDNF in the DBA/2J mouse, which develops chronic IOP elevation and subsequent loss of vision.…”
Section: Bdnf and Poagmentioning
confidence: 76%